FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH (SKPD) PEMERINTAH KOTA MAGELANG - Martinus Budiantara; Nugraeni Nugraeni (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study was to test empirically and analyzes the factors that influence the performance of managerial work units (SKPD) Magelang city government. These factors include participation in budgeting, budget goal clarity and decentralized structure. Management accountable local government, can not be separated from local government budgets. In preparing the budget, the government has implemented the participation of each unit of work in preparing the budget. The key to effective performance is the participation of subordinate plays an important role in achieving these objectives. Budget goal clarity illustrate the scope of the budget stated clearly and specifically, and understood by those responsible for their achievement. The existence of a clear budget targets will allow employees to draw up budgetary targets. Budget goal clarity will help employees to achieve the expected performance, which by knowing the budget target performance levels can be achieved. The more decentralized structure of government organizations in the region, the higher the head SKPD performance in running the financial management area. This led to research in the field of local government budgets, to be relevant and important. The study population was 26 Unit (SKPD) in the city of Magelang with a total sample of 75 people consisting of employees of accounting and budgeting. Data was collected by questionnaire and analyzed using multiple regression analysis. The result is that participation in budgeting, budget goal clarity and structure of decentralization affect the improvement of managerial performance SKPD either partially or simultaneously. Keyword: participation in budgeting, budget goal clarity, decentralized structure, managerial performance